Insights into remediation effects and bacterial diversity of different remediation measures in rare earth mine soil with SO42− and heavy metals - Yan, Xiao; Gao, Bowen; Wang, Jianlei; Zhu, Xuezhe; Zhang, Mingjiang (Frontiers in Microbiology, 2023)
The increased demand for rare earth resources has led to an increase in the development of rare earth mines (REMs). However, the production of high-concentration leaching agents (SO42−) and heavy metals as a result of rare earth mining has increased, necessitating the removal of contaminants. Here, a series of experiments with different remediation measures, including control (CK), sulfate-reducing bacteria (SRB) alone (M), chemicals (Ca(OH)2, 1.5 g/kg) plus SRB (CM-L), chemicals (Ca(OH)2, 3.0 g/kg) plus SRB (CM-M), and chemicals (Ca(OH)2, 4.5 g/kg) plus SRB (CM-H), were conducted to investigate the removal effect of SO42−, Pb, Zn, and Mn from the REM soil. Then, a high-throughput sequencing technology was applied to explore the response of bacterial community diversity and functions with different remediation measures. The results indicated that CM-M treatment had a more efficient removal effect for SO42−, Pb, Zn, and Mn than the others, up to 94.6, 88.3, 98.7, and 91%, respectively. Soil bacterial abundance and diversity were significantly affected by treatments with the inoculation of SRB in comparison with CK. The relative abundance of Desulfobacterota with the ability to transform SO42− into S2− increased significantly in all treatments, except for CK. There was a strong correlation between environmental factors (pH, Eh, SO42−, Pb, and Zn) and bacterial community structure. Furthermore, functional prediction analysis revealed that the SRB inoculation treatments significantly increased the abundance of sulfate respiration, sulfite respiration, and nitrogen fixation, while decreasing the abundance of manganese oxidation, dark hydrogen oxidation, and denitrification. This provides good evidence for us to understand the difference in removal efficiency, bacterial community structure, and function by different remediation measures that help select a more efficient and sustainable method to remediate contaminants in the REM soil.